Integration of visual context in early and late bilingual language processing: evidence from eye-tracking - Abashidze, Dato; Schmidt, Angela; Trofimovich, Pavel; Mercier, Julien (Frontiers in Psychology, 2023)
Previous research on the processing of language embedded in a rich visual context has revealed the strong effect that a recently viewed action event has on language comprehension. It has been shown that listeners are more likely to view the target object of a recently performed event than look at the target object of a plausible future event during sentence utterance, regardless of the tense cue. In the current visual-world eye-tracking experiments, we tested the strength of the recently observed visual context with a group of English monolingual and two groups of English–French early and late bilingual speakers. By comparing these different groups, we examined whether bilingual speakers, as a consequence of greater cognitive flexibility when integrating visual context and language information, show early anticipatory eye-movements towards the target object. We further asked whether early and late bilinguals show differences in their processing. The findings of the three eye-tracking experiments revealed an overall preference for the recently seen event. However, as a result of the early provision of tense cue, this preference was quickly diminished in all three groups. Moreover, the bilingual groups showed an earlier decrease in reliance on the recently seen event compared to monolingual speakers and the early bilinguals showed